2001
DOI: 10.1034/j.1399-3054.2001.1130303.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in phenol content during strawberry (Fragaria×ananassa, cv. Chandler) callus culture

Abstract: Total soluble phenols, soluble flavanols, (+)-catechin, ferulic acid and 1-O-feruloyl-beta-d-glucose were analyzed during the development of a strawberry (Fragariaxananassa, cv. Chandler) callus culture. The time-course changes of the different phenols assayed were well correlated with callus growth and morphology. The changes in polyphenol oxidase (EC 1.10.3.1-2) and beta-glucosidase (EC 3.2.1.21) activities in the callus were also examined. The total phenol, soluble flavanols and (+)-catechin contents were h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
59
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(66 citation statements)
references
References 42 publications
4
59
0
3
Order By: Relevance
“…Thus, accumulation of phenolic compounds in medium adversely affects the growth and survival of in vitro explants. [34,35] showed that accumulation of these compounds leads to browning and possibly death of the explants. Moreover, oxidized phenolic compounds may inhibit enzyme activity and result in the darkening of the culture medium and subsequent lethal browning of explants [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, accumulation of phenolic compounds in medium adversely affects the growth and survival of in vitro explants. [34,35] showed that accumulation of these compounds leads to browning and possibly death of the explants. Moreover, oxidized phenolic compounds may inhibit enzyme activity and result in the darkening of the culture medium and subsequent lethal browning of explants [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Total phenols in RG extracts were determined according to Arnaldos et al [22]. Specifically, RG (1 mL) was maintained in ice with pure methanol (1:1, v/v) for 30 min and centrifuged at 5,000g for 30 min at 4°C.…”
Section: Characterization Of the Productsmentioning
confidence: 99%
“…Phenolic compounds, especially oxidized phenolics, may contribute to the inhibition of enzymatic activities, resulting in the darkening of the culture medium and subsequent lethal browning of explants [32,33]. It has been reported that oxidized phenolics generally affect in vitro proliferation and regeneration negatively [34].…”
mentioning
confidence: 99%